PPARγ in Inflammatory Bowel Disease - Vito Annese; Francesca Rogai; Alessia Settesoldi; Siro Bagnoli (PPAR Research)
Peroxisome proliferator-activated receptor gamma (PPARγ) is member of a family of nuclear receptors that interacts with nuclear proteins acting as coactivators and corepressors. The colon is a major tissue which expresses PPARγ in epithelial cells and, to a lesser degree, in macrophages and lymphocytes and plays a role in the regulation of intestinal inflammation. Indeed, both natural and synthetic PPARγ ligands have beneficial effects in different models of experimental colitis, with possible implication in the therapy of inflammatory bowel disease (IBD). This paper will specifically focus on potential role of PPARγ in the predisposition and physiopathology of IBD and will analyze its possible role in medical therapy.